The Wild in Live Project: A Human/Algorithm learning network to help citizen science in wildlife conservation. - Simon, Alban Emmanuel Mazars (2019)
Dissertação de Mestrado em Ecologia apresentada à Faculdade de Ciências e Tecnologia